2022
DOI: 10.1055/a-1785-9290
|View full text |Cite
|
Sign up to set email alerts
|

Indication Creep of Antenatal Late Preterm Steroids

Abstract: While antenatal corticosteroids (ACS) administered in the late preterm period have been shown to reduce respiratory morbidity, this finding was demonstrated in a well-designed randomized controlled trial (ALPS) with strict inclusion/exclusion criteria that may differ from clinical practice. The aim of this study was to investigate whether there has been indication creep since use of late preterm ACS became standard of care. Retrospective cohort study of pregnant women who received late preterm ACS between 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…In the study by McElwee, et al, the highest rate of inappropriate exposure was for without cervical change (10), which is in contrast to our data where the No AS group had a higher incidence of PPROM compared to those who received AS. Pregestational diabetes was an exclusion criteria for ALPS study and SMFM recommendations, and our cohort expectedly showed a signi cantly larger proportion of diabetes in the No AS group compared to those given AS.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the study by McElwee, et al, the highest rate of inappropriate exposure was for without cervical change (10), which is in contrast to our data where the No AS group had a higher incidence of PPROM compared to those who received AS. Pregestational diabetes was an exclusion criteria for ALPS study and SMFM recommendations, and our cohort expectedly showed a signi cantly larger proportion of diabetes in the No AS group compared to those given AS.…”
Section: Discussioncontrasting
confidence: 99%
“…Only 4.5% of our AS group had pregestational diabetes, which was similar to the ndings of the cohort by McElwee, et al, where only 3% of inappropriate AS exposures were in the setting of pregestational diabetes. (10) This is in contrast to the ndings of Battarbee, et al, whose survey showed that greater than 50% of the providers reported administering betamethasone in the setting of poorly controlled diabetes or diabetes on insulin. ( 9)…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Obstetric practices, including those at our own institution, increasingly administered betamethasone for women at risk of late preterm delivery, within and outside of the criteria specified in the ALPS trial [ 7 – 9 ]. Though administration of ACS for twins and other deviations have been documented, the benefits remain unclear [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obstetric practices, including those at our own institution, increasingly administered betamethasone for women at risk of late preterm delivery, within and outside of the criteria specified in the ALPS trial [ 7 – 9 ]. Though administration of ACS for twins and other deviations have been documented, the benefits remain unclear [ 9 , 10 ]. Twins and singletons may have biological and pharmacokinetic differences [ 11 ], so findings from the ALPS trial may not be generalizable to twin gestations [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%